PENGARUH PENGERINGAN CONTOH TANAH TERHADAP BEBERAPA SIFAT FISIK DAN KIMJA TANAH BERSIFAT VERTIK SERTA KLASlFIKASINYA MENURUT TAKSONOMI TANAH - Djunaedi Abdul Rachim; Dyah Tjahjandari (Departemen Ilmu Tanah dan Sumberdaya Lahan, Fakultas Pertanian, IPB University, 1999)
This laboratory experiment was carried out to study the effect of soil samples drying on the physical and chemical properties of vertic soils and their classification according to soil taxonomy. Usually, soil analysis is held on samples in air-dried condition. Clays of some soil types, however, have irreversible properties upon drying which can cause a bias in the measurement results and classification outputs of the soils. To study the irreversibility of clays upon drying, 25 samples of vertic soils were treated in moist and air-dried conditions prior to analysis. The statistical procedure of Match Pair Comparison was used to test the effect of the treatments. The results showed that the irreversibility of day upon drying was reflected in the measured soil properties except for exchangeable-A! and -K, organic-C. and soil-CEC. Nevertheless, the intensity of the day irreversibility of the vertic soils studied was low. Therefore, the drying treatment did not affect their classification outputs.